An Analysis of the 2018 Karnataka General Assembly Elections' Systematic Voter Education and Electoral Participation Intervention (Journal of Advances and Scholarly Researches in Allied Education, 2025)
One of India's most prominent states, Karnataka, implemented a Systematic Voter Education and Electoral Participation (SVEEP) campaign in 2018. For the General Assembly Elections, this effort aimed to raise voter education and turnout. The objective of this article is to offer a critical assessment of the initiative's performance by examining the impact it has had on voter engagement, knowledge, and the democratic process overall. Using a wide range of communication channels, the Systematic Voters' Education and Election Engagement (SVEEP) program informs citizens, electors, and voters about the electoral process in an effort to raise their level of understanding and participation. As part of its design process, the SVEEP app considers the state's socioeconomic, cultural, and demographic features, as well as its electoral participation history and the lessons learned from previous rounds of elections. In order to overcome obstacles to voter registration, SVEEP tactics are designed and put into action. A few of these obstacles are conceptual in nature, while others stem from issues with the administration of voter registration or a dearth of pertinent information.